Implementing Azure Cloud design patterns : implement efficient design patterns for data management, high availability, monitoring, and other popular patterns on your Azure Cloud - Michalski, Oliver; Demiliani, Stefano (Packt Publishing, 2018)
Annotation A hands-on guide to mastering Azure cloud design patterns and best practices. Key FeaturesMaster architectural design patterns in Azure. Get hands-on with implementing design patterns. Implement best practices for improving efficiency and securityBook DescriptionA well designed cloud infrastructure covers factors such as consistency, maintenance, simplified administration and development, and reusability. Hence it is important to choose the right architectural pattern as it has a huge impact on the quality of cloud-hosted services. This book covers all Azure design patterns and functionalities to help you build your cloud infrastructure so it fits your system requirements. This book initially covers design patterns that are focused on factors such as availability and data management/monitoring. Then the focus shifts to complex design patterns such as multitasking, improving scalability, valet keys, and so on, with practical use cases. The book also supplies best practices to improve the security and performance of your cloud. By the end of this book, you will thoroughly be familiar with the different design and architectural patterns available with Windows Azure and capable of choosing the best pattern for your system. What you will learnLearn to organize Azure accessDesign the core areas of the Azure Execution ModelWork with storage and data managementCreate a health endpoint monitoring patternAutomate early detection of anomaliesIdentify and secure Azure featuresWho this book is forThis book is targeted at cloud architects and cloud solution providers who are looking for an extensive guide to implementing different patterns for the deployment and maintenance of services in Microsoft Azure. Prior experience with Azure is required as the book is completely focused on design patterns.
Keywords: Cloud computing.; Microsoft Azure (Computing platform); Infonuagique.; Microsoft Azure (Plateforme informatique); Computer architecture & logic design.; Computer networking & communications.; Computers -- System Administration -- General.; Computers -- Systems Architecture -- General.; Cloud computing